2022
DOI: 10.3390/nu14214460
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Walnut Intake on Lipids: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Cardiovascular diseases (CVD) are the leading causes of death worldwide. Dyslipidemia is a cardiometabolic risk factor of CVD, yet it can be modifiable. Walnuts have been suggested as a dietary intervention to improve the lipid profile. Therefore, we reviewed the literature to assess the evidence linking walnut intake to the improvement of blood lipids, including total cholesterol (TC), low-density lipoprotein (LDL-C) cholesterol, high-density lipoprotein (HDL-C) cholesterol, and triglycerides (TG). PubMed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The acquired results were also lower when compared to earlier studies examining the antioxidant activity of leaves, nuts, and walnut shells evaluated in the DPPH test (Pereira et al, 2007 , 2008 ). Natural antioxidants' primary function is to scavenge free radicals before they may trigger chain reactions in lipid‐rich matrices found in food, cosmetics, and pharmaceutical preparations, or in cell membranes (Alshahrani et al, 2022 ; Koşar et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquired results were also lower when compared to earlier studies examining the antioxidant activity of leaves, nuts, and walnut shells evaluated in the DPPH test (Pereira et al, 2007 , 2008 ). Natural antioxidants' primary function is to scavenge free radicals before they may trigger chain reactions in lipid‐rich matrices found in food, cosmetics, and pharmaceutical preparations, or in cell membranes (Alshahrani et al, 2022 ; Koşar et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Natural antioxidants' primary function is to scavenge free radicals before they may trigger chain reactions in lipid-rich matrices found in food, cosmetics, and pharmaceutical preparations, or in cell membranes (Alshahrani et al, 2022;Koşar et al, 2005).…”
Section: Ta B L E 1 Phenolic Compounds Detected Inmentioning
confidence: 99%
“…( 2012 ) demonstrated a significant increase in apolipoprotein A ( p = .03). Additionally, a recent meta‐analysis of randomized controlled trials showed an improvement in lipid profile, especially in obese/overweight patients (TC: −8.58 mg/dL, LDL: −5.68 mg/dL, TG: −10.94 mg/dL) (Alshahrani et al., 2022 ).…”
Section: Hyperlipidemiamentioning
confidence: 99%
“…All these properties have been related to the high content in bioactive compounds, such as phenolic compounds (quercetin, ellagic acid, ellagitannins, cyanidin and proanthocyanidins), phytosterols, γ-tocopherol, dietary fiber, protein (high L-arginine content), phytomelatonin and α-linolenic fatty acid [69,71]. Walnuts consumption has been associated with significant decreases in triglyceride, total cholesterol and LDL cholesterol contents in middle-aged and older adults [72]; this improvement in lipid profiles is associated with the reduction of cardiovascular diseases risk [70,73].…”
Section: Walnutsmentioning
confidence: 99%
“…Disease prevention and health promotion of walnuts intake in clinical trials seem to be prone to some bias, due to the wide dosage range, differences in diets among participants from different geographical regions and other defects in studies' design and methodology. For these reasons, including walnuts in one's diet probably has positive effects on health, although more investigations are needed [72,73].…”
Section: Walnutsmentioning
confidence: 99%